Our Potential and Challenges of Social Media in Promoting Women’s Health: Research Article (Journal of Advanced Research in Journalism & Mass Communication, 2020)
Women’s health is a matter of concern for very countries. The advancement in the field of internet and emergence of social media has affected communication process to a great extent. As social media has advantage over traditional media because of web-based applications, it can be used to promote health communication especially women’s health which is neglected over the time. The present article attempts to find out the potential and challenges of social media for using as a tool to promote and aware the public on women’s health. How to cite this article: Pandey N. Our Potential and Challenges of Social Media in Promoting Women’s Health. J Adv Res Jrnl Mass Comm 2020; 7(1): 4-7. DOI: https://doi.org/10.24321/2395.3810.202002